2011
DOI: 10.1080/10410236.2011.560797
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Protective Effects of Brand Equity in thekeepin' it REALSubstance Use Prevention Curriculum

Abstract: While branding appears to be an effective health prevention strategy, it is less clear how successful brands have protective effects. To better understand the role of branding in health prevention and promotion, it is necessary to examine how the persuasive mechanisms of branding function in health campaigns (e.g., modeling socially desirable behaviors). Using a cross-sectional data (N = 709), the current study uncovered the mechanisms explaining branding’s effects on adolescent substance use in a school-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…The brand equity model findings were consistent with our stated hypothesis, were replicated over the evaluation period, and were similar to other studies (Evans et al, 2005; Evans et al, 2011; Lee & Hecht, 2011; Price et al, 2009). Brand equity accounted for covariance between ad message exposure and PS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The brand equity model findings were consistent with our stated hypothesis, were replicated over the evaluation period, and were similar to other studies (Evans et al, 2005; Evans et al, 2011; Lee & Hecht, 2011; Price et al, 2009). Brand equity accounted for covariance between ad message exposure and PS.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, brand equity was found to account for covariance in the relationship between message exposure and PS, suggesting a potential mechanism for brand equity in improving the effectiveness of social marketing campaigns. The brand equity model findings were consistent with our stated hypothesis, were replicated over the evaluation period, and were similar to other studies (Evans et al, 2005;Evans et al, 2011;Lee & Hecht, 2011;Price et al, 2009). Brand equity accounted for covariance between ad message exposure and PS.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Exposure to the truth SM ads depicting the positive images of nonsmoking was associated with a decline in the youth smoking rate (Evans & Hastings, 2008; Evans et al, 2005). Although recent studies have indicated the effectiveness of marketing and communication efforts to build various health brands (Evans et al, 2005; Huhman et al, 2005; Lee & Hecht, 2011), little is known about how to create and develop a strong brand for smoking cessation services. This article describes ClearWay Minnesota’s approach to developing the QUITPLAN cessation services brand and presents findings from a study that examines the impact of television advertising on brand-related cognitions and intentions to quit among smokers.…”
Section: Introductionmentioning
confidence: 99%